An Introduction to Mill's Utilitarian Ethics. - West, Henry (Cambridge University Press, 2003)
John Stuart Mill was the leading British philosopher of the nineteenth century and his famous essay Utilitarianism is the most influential statement of this philosophical approach. Henry West's introduction to utilitarianism serves as both a commentary to, and interpretation of, the text.